An industrial Quality Control Study on J. F. Rubber Philippines, Inc. - Bunao, Lucky Gil (College of Engineering, 2006)
J.F. Rubber Philippines, Inc. is a company engaged in rubber production which has been granted with the ISO 9002:1994 and QS 9000:1998 (based on and including ISO 9002:1994). The aim of this study is to improve J.F. Rubber?s product and service quality through the basic concepts and principles of Statistical Process Control. After having interviews with the Production and QA manager, the group focused on how to manufacture the products 8327 and 8328, products which have high consistent demand and give the most number of rejects. Failure Mode and Effects Analysis and the Pareto Diagram were used to identify the main causes for rejects. From there, Release Marks and Air Checks were known to be the two most occurring rejects. A cause and effect diagram was made, and it showed that most of the rejects were due to human factors. Also, the four critical variables for the curing process were analyzed by using X-bar and S control charts to determine further the sources of problems. Based on these charts, the main assignable causes for the out of control points include (1) temporary change in the raw material used, (2) high temperature, and (3) drop in the temperature due to wrong setting, maintenance, and heater wattage. Process Capability Analysis was used to analyze the control charts. For part number 8327 and 8328, the process capability ratio, Cp, values for the lower and upper temperature are less than 1.33. Thus, the processes for the two products are incapable. Percentages of the specification band used up by the curing process show that the company will produce a sizeable amount of nonconforming products. Analysis of the process actual capability, Cpk, indicates that both processes are off-centered. The two acceptance sampling plans the company currently uses were also analyzed. It was found out that there have been deviations in the sample size as compared to the MIL STD 105E. These deviations could increase either the producer?s risk (if the sample is greater than that of the MIL STD) or the consumer?s risk (if it is lesser). In order to address the problems, the group came up with the four major recommendations: (1) improve data collection and monitoring of variables through the use alternative measuring devices and improvement of maintenance procedure to ensure that the information, which is used for evaluation, obtained has fewer discrepancies, (2) apply methods engineering tools to the curing process, such as reevaluation of the machine-product line, analysis of therbligs on the process to eliminate ineffective motions, and conducting an ergonomic study on the process to further improve the working conditions (3) re-evaluate acceptance sampling plans and use the original sample size indicated in the MIL STD 105E to lessen the chances of having producer?s and consumer?s risk, and (4) continuous involvement of the management to the production process, with ways such as training and continuously training workers for the mastery of the whole process of a certain operation, developing a staff scheduling system to make sure that the workers assigned to a certain field of operation are experts n that field, strict observance on hazard avoidance, and further improvement of the working environment through constant worker management dialogue to make it hazard-free and more conducive to working.